Long‐Term Effects of Sglt2 Deletion on Bone and Mineral Metabolism in Mice. (6th July 2021) - Gerber, Claire; Wang, Xueyan; David, Valentin; Quaggin, Susan E.; Isakova, Tamara; Martin, Aline
ABSTRACT: Sodium‐glucose cotransporter 2 (SGLT2) inhibitors improve kidney and cardiovascular outcomes in patients with type 2 diabetes mellitus (T2DM). However, bone fragility has emerged as a side effect in some but not in all human studies. Because use of SGLT2 inhibitors in humans affects mineral metabolism, we investigated the long‐term effects of genetic loss of Sglt2 function on bone and mineral metabolism in mice. Slc5a2 nonsense mutation in Sweet Pee (SP) mice results in total loss of Sglt2 function. We collected urine, serum, and bone samples from 15‐week‐old and 25‐week‐old wild‐type (WT) and SP mice fasted from food overnight. We measured parameters of renal function and mineral metabolism and we assessed bone growth, microarchitecture, and mineralization. As expected, 15‐week‐old and 25‐week‐old SP mice showed increased glucosuria, and normal kidney function compared to age‐matched WT mice. At 15 weeks, SP mice did not show alterations in mineral metabolism parameters. At 25 weeks, SP mice showed reduced fasting 24‐hour urinary calcium excretion and increased fractional excretion of phosphate, but normal serum calcium and phosphate, parathyroid hormone (PTH), vitamin D (1, 25(OH)2 D), and fibroblast growth factor (FGF23) levels. At 25 weeks, but not at 15 weeks, SP mice showed reduced body weight compared to WT. This was associated with reduced femur length at 25 weeks, suggesting impaired skeletal growth. SP mice did not show trabecular or cortical bone microarchitectural modifications but showed reduced cortical bone mineral density compared to WT mice at 25 weeks. These results suggest that loss of Sglt2 function in mice in the absence of T2DM does not alter regulatory hormones FGF23, PTH, and 1, 25(OH)2 D, but may contribute to bone fragility over the long term. Future studies are required to determine how loss of Sglt2 function impacts bone fragility in T2DM. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.